Small Agricultural Household: The Subject of the Modernization of Agricultural Production and Management in China - Jianguo Zhang (Journal of Theory and Practice in Humanities and Social Sciences, 2023)
The subject of agricultural production and management in China has always been Small agricultural household, rather than individuals or collectives; this model will not disappear for a long period of time. The current subject of agricultural production and management in China is the Small agricultural household model that has been continued for more than two thousand years, and the contents of Small agricultural household production and management contributed to the initial targets of agricultural production and management, namely intensive cultivation and self-sufficiency. Traditional Small agricultural household production and management model is not completely consistent with the industrial goal of the present agricultural modernization. In particular, second rounds of land transfer and contract solidified the scale of agricultural operation and influenced the industrial transformation of agricultural development. Influenced by market-oriented economy, farmer households drive the innovation of Small agricultural household production and management model, so the next focus of Chinese reform of the subject of agricultural production and management should be fitting into the goal of agricultural modernization and correctly understanding the status of Small agricultural household; meanwhile, the subject of agricultural production and the subject of management should be separated appropriately.